THE DEFINITIVE GUIDE TO SUPPLY CHAIN BEST PRACTICES COMPREHENSIVE LESSONS AND CASES IN EFFECTIVE SCM - Frankel, Robert M. (Council of supply chain management professionals series, 2014)
The Council of Supply Chain Management Professionals (CSCMP) brings together state-of-the-art supply chain management case studies to help readers systematically identify challenges, evaluate solutions, plan implementation, and prepare for the future. Commissioned by CSCMP, these realistic, fact-based cases are written by world-renowned experts, and reflect the full complexity of modern supply chain/demand chain/logistics management. Coverage includes: supply chain collaboration, advanced forecasting, management of inventory through cash-to-cash cycles, transportation optimization, and many other topics. Readers are effectively challenged to evaluate each scenario and identify the responses most likely to succeed. As they do so, they will encounter the field's newest best practices. Even more important, they will learn how to integrate a wide array of functional activities, from forecasting and demand planning through order fulfillment and post-sales service. Using these cases, students and professionals will become familiar with a far wider range of scenarios - enabling them to solve more problems, succeed in new environments, and prepare for faster career growth.